2021
DOI: 10.2489/jswc.2021.02158
|View full text |Cite
|
Sign up to set email alerts
|

Soil health conceptualization differs across key stakeholder groups in the Midwest

Abstract: Stakeholder conceptualizations of soil health inform agricultural decision-making. Currently, diverse sources of soil health knowledge have resulted in divergent conceptualizations of soil health across groups. Using a combination of mail and online surveys of corn (Zea mays L.), soybean (Glycine max [L.] Merr.), and wheat (Tritcum aestivum L.) farmers (n = 89); USDA Natural Resources Conservation Service (NRCS) personnel (n = 134); and agricultural researchers (n = 42) in the Midwest; we (1) investigated how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…As per this definition, soil health metrics were developed to provide a holistic view of the complex, multi‐faceted functions in the soil system. Farmer‐level interest is clear, with the expansion of soil health analysis offered in soil test laboratories and increased interest in soil health management practices (Gruver & Weil, 2007; Moebius‐Clune et al., 2016; Stewart et al., 2018; Wade et al., 2021). Parallel with this movement, considerable research efforts have identified soil analyses that reflect improvements in soil biological properties from the adoption of conservation land use practices.…”
Section: Introductionmentioning
confidence: 99%
“…As per this definition, soil health metrics were developed to provide a holistic view of the complex, multi‐faceted functions in the soil system. Farmer‐level interest is clear, with the expansion of soil health analysis offered in soil test laboratories and increased interest in soil health management practices (Gruver & Weil, 2007; Moebius‐Clune et al., 2016; Stewart et al., 2018; Wade et al., 2021). Parallel with this movement, considerable research efforts have identified soil analyses that reflect improvements in soil biological properties from the adoption of conservation land use practices.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the short-term shifts of soil C and N following conversion may better inform farmers, researchers, and policymakers to design best management practices and programs that consider key ecosystem services, including SOC sequestration. As identified in a recent survey, soil organic matter (SOM) was one of the most common soil tests conducted and provided the most valuable information to farmers and researchers (Wade et al 2021). Additionally, labile organic matter pools associated with soil microbes (e.g., microbial biomass), their C sources (e.g., particulate organic matter) and activities (e.g., respiration and the release of CO 2 ) provide greater insights into the flow of C through the system and can be early indicators of C sequestration (Lehmann and Kleber 2015;Moore-Kucera et al 2008).…”
mentioning
confidence: 99%
“…The utilization of N fertilizer in crop production can influence soil health indirectly and in the longer term through changes in OM content, and directly and in the shorter term via pH changes (Singh, 2018). Recently, it was found that Midwestern grain farmers conceptualize improved soil health to entail lower nutrient losses and to decrease the need for inputs such as N fertilizer to achieve the same yield (Wade et al., 2021). Testing this farmer‐conceptualized relationship in the tile‐drained agroecosystems of the US Midwest under diverse N‐fertilization rates may provide insights into linkages among soil health, nitrate‐N losses, and crop productivity.…”
Section: Introductionmentioning
confidence: 99%